2014
DOI: 10.1021/am5055228
|View full text |Cite
|
Sign up to set email alerts
|

Composite of Macroporous Carbon with Honeycomb-Like Structure from Mollusc Shell and NiCo2O4 Nanowires for High-Performance Supercapacitor

Abstract: Novel biological carbon materials with highly ordered microstructure and large pore volume have caused great interest due to their multifunctional properties. Herein, we report the preparation of an interconnected porous carbon material by carbonizing the organic matrix of mollusc shell. The obtained three-dimensional carbon skeleton consists of hexangular and tightly arranged channels, which endow it with efficient electrolyte penetration and fast electron transfer, enable the mollusc shell based macroporous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(48 citation statements)
references
References 42 publications
2
46
0
Order By: Relevance
“…It can be observed that the specific capacitance gradually increases in the course of initial 500 cycles instead of decreasing. This phenomenon can be attributed to the full activation of the electrodes and also appears in many cycling stability tests in the literatures (Xiong et al 2014;Liang et al 2014). More importantly, the CoNiO 2 //AC ASCs exhibit better cycling performance at each current density.…”
Section: Electrochemical Performances Of Asymmetric Supercapacitors Bmentioning
confidence: 65%
“…It can be observed that the specific capacitance gradually increases in the course of initial 500 cycles instead of decreasing. This phenomenon can be attributed to the full activation of the electrodes and also appears in many cycling stability tests in the literatures (Xiong et al 2014;Liang et al 2014). More importantly, the CoNiO 2 //AC ASCs exhibit better cycling performance at each current density.…”
Section: Electrochemical Performances Of Asymmetric Supercapacitors Bmentioning
confidence: 65%
“…Aniline (1 mL) was dissolved in 54 mL of H 2 SO 4 (0.5 M) and stirred well in an ice bath. Certain amounts of NiCo 2 O 4 (5,8,10,15, and 20 wt%) nanopowder were suspended in the above solution and stirred for about 1 h. As an oxidizing agent, 50 mL of precooled solution of ammonium persulfate (0.1 M) was then slowly added drop wise to the mixture with a constant stirring over a period of 2 h. The reaction was then left at 0°C for 4 h. The product obtained was collected by filtration and washed several times by acetone and distilled water until the filtrate was colorless. The product was dried at 80°C for 24 h. Pure polyaniline was synthesized in the same manner without adding NiCo 2 O 4 .…”
Section: Methodsmentioning
confidence: 99%
“…Active materials are the most crucial factor in governing the electrochemical performance for supercapacitors. Generally, the active materials have three kinds including carbon materials [4,5], conducting polymers [6,7], and transition metal oxides [8,9]. Among all these materials mentioned above, conducting polymers are the most promising materials as they possess redox pseudocapacitance in addition to double-layer capacitance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[142] Furthermore, the restacking and aggregation of some 1D and two-dimensional (2D) carbon materials, such as GN and CNTs, can cause severe degradation of the electrochemical properties due to the strong van der Waals interactions between the neighboring layers. [143] Hence, lowcost biochars with delicate structures have been studied as raw materials to fabricate metallic oxide/carbon (NiO/C, [140a] Co 3 O 4 /C, [144] NiCo 2 O 4 /C, [145] MnO 2 /C, [146] etc. ), metallic hydroxide/carbon (Ni-Al layered double hydroxide/C [143b] ), Adv.…”
Section: Biochar Based Compositesmentioning
confidence: 99%